"Breaking the mirror": interface innovation and market capture by Japanese professional camera firms, 1955–1974. (4th March 2019) - Windrum, Paul; Haynes, Michelle; Thompson, Peter
Abstract: Improving an interface to increase control over interactions between existing product modules can create new product features which alter the basis of competition in mature (sub)markets. We empirically examine the impact of interface innovation by new market entrants from Japan in the high-end, professional camera submarket between 1955 and 1974. Prior to 1960, the industry architecture of the professional camera submarket was modular, dominated by German specialist body and specialist lens manufacturers. This market structure changed due to the success of integrated Japanese startups who, from 1961, offered novel automated exposure features, facilitated by improving the existing interface between the camera body and lens, and by making this interface a proprietary standard. Their success broke the mirror between the industry architecture, which became vertically integrated, while the product architecture remained modular.